Managing Chronic Diseases: Diabetes Mellitus - Ruby Bhadoriya (International Journal of Antibiotics, 2026)
Diabetes mellitus is one of the most prevalent chronic non-communicable diseases worldwide and represents a major public health challenge due to its long-term complications, increasing prevalence, and economic burden on individuals and healthcare systems. It is distinguished by chronic hyperglycemia brought on by deficiencies in either insulin action or secretion, or both. Diabetes causes increasing harm to several organ systems, including the kidneys, eyes, neurological system, and cardiovascular system, if it is not well managed. Effective management of diabetes requires a comprehensive and multidisciplinary approach that integrates lifestyle modification, pharmacological therapy, patient education, regular monitoring, and prevention of complications. Nurses play a crucial role in patient care through education, monitoring, emotional support, and promotion of adherence to treatment. This article provides an in-depth overview of diabetes mellitus, including its classification, etiology, pathophysiology, clinical manifestations, diagnostic criteria, management strategies, nursing care, prevention, and patient self-management. Emphasis is placed on holistic long-term care approaches aimed at improving quality of life and reducing morbidity and mortality associated with diabetes.
Keywords: Complications; Diabetes mellitus; chronic disease management; insulin therapy; lifestyle modification; nursing care; patient education